Consultation skills for the MRCGP - Naidoo, P. (Prashini) (Scion Pub., 2012)
This book helps readers pull together the knowledge and communication skills required for success in the consultation components of the MRCGP exam, namely Clinical Skills Assessment (CSA) and Clinical Observation Tool (COT). The book does this in three ways: * by demonstrating some of the required consultation skills on the accompanying DVD, which features 13 typical consultations * by identifying and teaching these skills in a further 20 case write-ups - these offer readers an ordered, step-wise approach to data gathering, clinical management and interpersonal skills * by giving candidates 15 'practice cases' (completely new for the second edition) for use either alone or in small groups - these cases now feature marking schemes. The book and DVD are meant to be interactive, with some of the DVD cases being accompanied by a CSA marking schedule for readers to assess the candidate's performance. Readers are asked if the doctor on the DVD: * asked the right questions, at the right time, in the right way * performed the right examination correctly * communicated in a precise, understandable and sensitive manner.